CONTAGION EFFECT AND ORGANIZATION - Wycislak, Slawomir (European Scientific Journal, ESJ, 2014)
The idea behind the article is to explain the mechanism behind the contagion and characterize the response models of organization. Initially, the term contagion was used within immunology, and has attracted considerable interest in psychology, sociology and research into financial crises as well as into the way various effects spread throughout networks of companies. However, models of response of organization towards contagion are rarely analyzed. The article identifies attributes of contagion as well as definition and types of contagion. What is more, the paper shows the methodology for the diagnosis of contagion within the organization activities. In the final part of the article two models of organization’s response to contagion are discussed. One of them is based on the metaphor to the response of the immune system to the disturbance factor.